2020
DOI: 10.11591/eei.v9i3.1916
|View full text |Cite
|
Sign up to set email alerts
|

Satellite imagery and machine learning for aridity disaster classification using vegetation indices

Abstract: Central Java Province is one of provinces in Indonesia that has a high aridity risk index. Aridity disaster risk monitoring and detection can be done more accurately in larger areas and with lower costs if the vegetation index is extracted from the remote sensing imagery. This study aims to provide accurate aridity risk index information using spectral vegetation index data obtained from LANDSAT 8 OLI satellite. The classification of drought risk areas was carried out using k-nn with the Spatial Autocorrelatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…In this section, some research about remote sensing based on prediction and classification are discussed. Prasetyo et al (2020) implemented spectral vegetation index to the data obtained from the Landsat 8 OLI satellite to provide disaster risk index information. k -NN with spatial autocorrelation was used to classify the drought risk areas.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, some research about remote sensing based on prediction and classification are discussed. Prasetyo et al (2020) implemented spectral vegetation index to the data obtained from the Landsat 8 OLI satellite to provide disaster risk index information. k -NN with spatial autocorrelation was used to classify the drought risk areas.…”
Section: Related Workmentioning
confidence: 99%
“…In summary, it has been shown from this review that spectral vegetation indices indicated the quantitative values for measuring the vegetation canopy in receiving and reflecting the light spectrum. They were interpreted as plant’s spectral characteristics, including the infrared spectrum as visible light (IR) and the near infrared spectrum as invisible light (NIR) ( Prasetyo et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…Random Forest merupakan metode ensemble untuk klasifikasi dan regresi penentuan wilayah gambar dan pembuatan variable dari berbagai model untuk menghitung respon berdasarkan hasil dari pohon keputusan [21] [23]. Setelah dilakukan klasifikasi dan prediksi menggunakan algoritma random forest maka dilakukan uji performa klasifikasi dengan menggunakan Cohen's Kappa yang akan menghasilkan nilai akurasi [24].…”
Section: Random Forestunclassified
“…The (Prasetyo, Hartomo, Paseleng, Chandra, & E. Winarko, 2020). Based on the government's policies, it is necessary to re-evaluate to find the best solution to avoid land and forest fires.…”
Section: Introductionmentioning
confidence: 99%